Crystallographic analysis on atomic-plane parallelisms between bcc precipitates and hcp matrix in recrystallized Zr-2.5Nb alloys. (March 2017) - Matsukawa, Y.; Okuma, I.; Muta, H.; Shinohara, Y.; Suzue, R.; Yang, H.L.; Maruyama, T.; Toyama, T.; Shen, J.J.; Li, Y.F.; Satoh, Y.; Yamanaka, S.; et al.
Abstract: The crystal orientation of body centered cubic (bcc) precipitates embedded in hexagonal close packed (hcp) matrix is usually assumed to follow the so-called Burgers orientation relationship; however, this orientation relationship may not be maintained in the case where the precipitation occurs in parallel with the recrystallization of matrix. The Zr-2.5Nb alloy is a typical example of such a case. In the present study crystal orientations of bcc precipitates (Nb-rich β2 phase and Zr-rich β1 phase) in fully recrystallized hcp Zr matrix have been analyzed by means of electron backscatter diffraction (EBSD) and transmission Kikuchi diffraction (TKD). Based on the Euler angles determined by EBSD/TKD, the parallelism of atomic planes was examined one by one. The analysis was performed on 100 precipitates for each composition. The crystal orientations of the Nb-rich precipitates were practically random, whereas 28% of the Zr-rich precipitates followed the Burgers orientation relationship. Moreover, the fraction of the Nb-rich precipitates whose slip planes, either {110} or {112}, were parallel to those of the hcp Zr matrix, { 10 1 ¯ 0 }, was no greater than 5%. These results support a tentative conclusion of our previous study that the Nb precipitates are ideal Orowan type strong obstacles against gliding dislocations due to the crystal mismatch, even though they are softer than the matrix in terms of shear modulus. Graphical abstract: Image 1